2004
DOI: 10.2307/3762061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Studies on the Diatrypaceae Based on rDNA-ITS Sequences

Abstract: The order Diatrypales (Ascomycota) contains one single family, the Diatrypaceae. To obtain insight in the phylogenetic relationships within this family, the complete sequences of the ITS region (ITS1, 5.8S rRNA gene and ITS2) of 53 isolates from the five main genera in the family (Diatrype, Diatrypella, Cryptosphaeria, Eutypa and Eutypella) were determined and aligned for phylogenetic reconstruction. Sequence analysis revealed the presence of tandem repeated motifs 11 nucleotides-long, placed in homologous pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 10 publications
8
28
0
Order By: Relevance
“…Nitschke 1867 Note -Diatrypella is feature characterized by "ascostromata conical or truncate, cushion-like or discoid, usually delimited by a black zone on host tissues, perithecial ascomata, umbilicate or sulcate ostioles; asci polysporous, cylindrical, with long stalks and ascospores are ovoid to allantoid, hyaline or yellowish" (Vasilyeva & Stephenson 2005, Mehrabi et al 2015, Shang et al 2017. Acero et al (2004) confirmed the polyphyletic groups of Diatrypella in Diatrypaceae based on phylogenetic analysis of ITS rDNA data and this was concurred from previous studies (de Almeida et al 2016, Mehrabi et al 2016, Shang et al 2017. 1 -Phylogram generated from the best scoring of the RAxML tree based on a combined ITS and β-tubulin sequence data.…”
Section: Allocryptovalsa Polysporasupporting
confidence: 90%
See 2 more Smart Citations
“…Nitschke 1867 Note -Diatrypella is feature characterized by "ascostromata conical or truncate, cushion-like or discoid, usually delimited by a black zone on host tissues, perithecial ascomata, umbilicate or sulcate ostioles; asci polysporous, cylindrical, with long stalks and ascospores are ovoid to allantoid, hyaline or yellowish" (Vasilyeva & Stephenson 2005, Mehrabi et al 2015, Shang et al 2017. Acero et al (2004) confirmed the polyphyletic groups of Diatrypella in Diatrypaceae based on phylogenetic analysis of ITS rDNA data and this was concurred from previous studies (de Almeida et al 2016, Mehrabi et al 2016, Shang et al 2017. 1 -Phylogram generated from the best scoring of the RAxML tree based on a combined ITS and β-tubulin sequence data.…”
Section: Allocryptovalsa Polysporasupporting
confidence: 90%
“…Taxa in Diatrypaceae are difficult to distinguish based on the morphological characters (Acero et al 2004, Vasilyeva & Stephenson 2005. Therefore, multigene phylogenetic investigations are needed to clarify phylogenetic affinities of the genera in this family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses confirm the observation by Acero et al (2004) that the current taxonomic scheme for the Diatrypaceae may not reflect the true evolutionary relationships of these fungi and limits between genera. Moreover, the present analyses did not allow the evolutionary history of Diatrypaceae to be elucidated, as bootstrap values were small at deep nodes within the various tree topologies.…”
Section: Discussionsupporting
confidence: 71%
“…The current classification of diatrypaceous genera remains provisional and there is an urgent need to revise the classification of the family and test the significance of generic concepts using molecular phylogeny. Preliminary attempts at phylogenetic classification using molecular data as well as morphological characters remained inconclusive regarding the evolutionary relationships of these fungi (Acero et al 2004;Carmarán et al 2006;Trouillas et al 2010a, b). In Australia, little work has been conducted to investigate the diversity and taxonomy of diatrypaceous fungi.…”
Section: Introductionmentioning
confidence: 99%